Bile‐Derived Organoids From Patients With Primary Sclerosing Cholangitis Recapitulate Their Inflammatory Immune Profile. Issue 3 (13th March 2019) - Soroka, Carol J.; Assis, David N.; Alrabadi, Leina S.; Roberts, Scott; Cusack, Laura; Jaffe, Ariel B.; Boyer, James L.
Abstract : Primary sclerosing cholangitis (PSC) is a heterogeneous and progressive fibroinflammatory cholangiopathy with no known etiology or effective treatment. Studies of PSC are limited due to difficulty in accessing the cholangiocyte, the small percentage of these cells in the liver, instability of in vitro culture systems, and reliance on samples from end‐stage disease. Here, we demonstrate that stem cells can be isolated from the bile of PSC patients undergoing endoscopic retrograde cholangiopancreatography earlier in their clinical course and maintained long term in vitro as three‐dimensional (3D) organoids that express a biliary genetic phenotype. Additionally, bile‐derived organoids (BDOs) can be biobanked and samples obtained longitudinally over the course of the disease. These BDOs express known cholangiocyte markers including gamma glutamyl transferase, cytokeratin 19, epithelial cellular adhesion molecule, cystic fibrosis transmembrane conductance regulator, and anion exchanger 2. RNA sequence analysis identified 39 genes whose expression differed in organoids from PSC patients compared to non‐PSC controls, including human leukocyte antigen DM alpha chain and chemokine (C‐C motif) ligand 20 (CCL20), immune‐related genes previously described in genome‐wide association studies of PSC. Incubation of these BDOs with interleukin 17A or tumor necrosis factor alpha led to an immune‐reactive phenotype with a significant increase in secretion of proinflammatory mediators, including CCL20, a T‐cell chemoattractant. Conclusion : This study demonstrates that bile can be used as a source of biliary‐like cells that can be maintained long term in vitro as 3D organoids; these BDOs retain features of cholangiopathies, including the ability to react to inflammatory stimuli by secreting chemokines and propagating an immune‐reactive phenotype reflective of the pathogenesis of these diseases; thus, BDOs represent a platform for the study of the pathogenesis and therapy of cholangiopathies, particularly PSC.